2011
DOI: 10.2215/cjn.04730510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Phosphate and Calcium Intake on Fibroblast Growth Factor-23

Abstract: SummaryBackground and objectives Little is known about the influence of dietary phosphate intake on fibroblast growth factor-23 (FGF23) and its subsequent effects on vitamin D levels. This study addresses changes in intact FGF23 (iFGF23) and C-terminal FGF23 (cFGF23), phosphaturia, and levels of vitamin D on high and low phosphate and calcium intake.Design, setting, participants, & measurements Ten healthy subjects adhered to a diet low or high in phosphate and calcium content for 36 hours each with a 1-week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
3
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(156 citation statements)
references
References 32 publications
6
137
3
9
Order By: Relevance
“…Finally, we were unable to examine whether diurnal changes in FGF23 throughout the morning might have affected changes in FGF23 levels during the infusion period. However, given a recent study showing that FGF23 levels, if anything, increase during the morning and early afternoon in healthy volunteers (28), diurnal changes are unlikely to explain the decrease in FGF23 in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Finally, we were unable to examine whether diurnal changes in FGF23 throughout the morning might have affected changes in FGF23 levels during the infusion period. However, given a recent study showing that FGF23 levels, if anything, increase during the morning and early afternoon in healthy volunteers (28), diurnal changes are unlikely to explain the decrease in FGF23 in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…We previously reported no postprandial changes in FGF23 (6), which were confirmed here. In contrast, a single study of 10 healthy volunteers, in whom FGF23 levels were measured three times during the day, found that there was some circadian variability in FGF23 levels, with a rise in mean (6SE) cFGF23 levels from 45627 to 68645 reference units/ml at the end of the day (27). Taken together, the findings to date seem to indicate that, if circadian variability in FGF23 levels does exist, it is likely of very low amplitude.…”
Section: Discussionmentioning
confidence: 83%
“…Figure 4 illustrates how both serum phosphate and PTH fluctuate with an inherent biphasic pattern, peaking in the afternoon and late evening but readjusting to the morning fasting concentration of the previous day (indicated by the arrows). This phenomenon of readjusting to the morning fasting concentration of the previous day has been shown for serum phosphate (16,(42)(43)(44), PTH (16,43), and, although less convincingly, FGF-23 (41,45). The need for multiple serum sampling to monitor dietary phosphorus effects on calcium and phosphorus balance was first suggested by Smith and Nordin in 1964 (42), when they were unable to demonstrate a change in serum calcium or phosphate concentrations in response to phosphorus intake using a single daily blood sampling.…”
Section: Masking Of Diet-related Changes In Serum Phosphorus Pth Anmentioning
confidence: 79%